DEVELOPMENT OF ARTIFICIAL INTELLIGENCE IN THE SPHERE OF EDUCATION: EDUCOLOGICAL ASPECTS - Olga Melnychenko (Неперервна професійна освіта: теорія та практика)
The article is devoted to the analysis of the positive and negative effects of artificial intelligence on the development of education, which is done with the help of educology and a synergistic approach. The author emphasizes that this methodology integrates knowledge about education and the educational sphere as a whole, and is an interdisciplinary direction of scientific development based on numerous methods borrowed from natural sciences, cybernetics, mathematical sciences, etc. The author notes that both educology and synergetic help to imagine the modern field of education as a synergistic system, that is, one that exists in interconnection and interaction with other open systems. Such a view changes the perception of manifestations of randomness and necessity in educational systems, the irreversibility of educational processes, and allows us to understand in a different way the nature and essence of chaotic processes in educational systems, using the example of modern information and communication technologies, and artificial intelligence in particular. The author proves that artificial intelligence is becoming a mega-fluctuation of society today, which will not only change the contours of the future, but also become a bifurcation point for humanity. The author analyzed the positive and negative effects of artificial intelligence on education, made a comparative table of these manifestations in the educational, scientific, communicative, ethical and social spheres. The author paid special attention to the social aspects of the negative impact of the use of artificial intelligence in education: control over the opinions of students and teachers, the creation and distribution of fakes; rewriting huge chunks of reality or hiding uncomfortable truths; inclination of students to «correct», standard thinking; promoting the destruction of certain types of specialties, etc. The author presents recommendations for mitigating the negative effects of artificial intelligence on education. According to the author, one of the main conditions for mitigating the negative effects of AI on the development of education is recognizаtion the need to study basic knowledge, facts, writing, calculations, etc. It is the task of educators to develop ways in which they can help students learn the facts and master the foundations of knowledge in more traditional curriculum subjects such as mathematics or English. The next recommendation expressed by the author is the involvement of students in the discussion of the negative consequences of the development of AI in education. It is necessary to ask students to analyze situations in which it is possible to use AI, and in which it prevents the development of necessary skills or creates injustice in the learning process. It is possible to involve students of various specialties in drawing up instructions on the use of AI in higher education. For this, students need to familiarize themselves with the articles of various scientists and working groups and commissions that consider the same issues. Not only will this turn AI into a learning component, but it will also help students feel responsible for following those instructions: students will be much more likely to follow instructions they help develop, rather than those imposed on them. In general, taking into account the numerous positive and negative effects of AI on the development of education, the author comes to the conclusion that adapting the best properties and ways of using artificial intelligence to traditional institutional and educational practices and developing strict ethical norms can create the best results of using artificial intelligence for students, teachers and education managers.